a=b ab=b^2 ab-a^2=b^2-a^2 a(b-a)=(b-a)(b+a) a=(a+b) a=2a a=2a, and a=1 then 1=2. If 1=2 then 1+1=3 As you can see, 1+1=3.

but if b=1 and a = anything but 1, you can't say a=b. LOL, Kazzy backed out. and serbs, I was already on my second year of algebra when I was your age. I'm taking calc this year, I know algebra.

1=1 as well, as stated in the first statement of a=b. So 1=1 and 2. 1 can equal 3 if I want to, and since 3 is a better number than 4, I choose three.

you never defined which instance of 1 u were using in each occurance of it in that statement. therfore my conclusion is also correct, and my insult holds.

Step four: you obtain the result in step five by dividing (b-a). If a=b, then that equals zero, and the equation is undefined. Q.E.D, bitch.